Educational Exchange and New Opportunities – The Perspectives of Polish Erasmus Students in Portugal - Wiśniewski, Rafał; Bukalska, Izabela (Seminare : poszukiwania naukowe, 2022)
The Erasmus Programme was officially introduced in 1987 despite the discontent of some member states which had their own solutions in the field of educational exchange. Instead, the new programme was supposed to achieve certain far- reaching goals which exceeded the interests of particular countries.  Achieving the goals of the program involved some difficulties because the process initiated by the student exchange program last several years and should be consistent with changes taking place at that time in the field of education. Furthermore, the overall objectives should harmonize with the interests of individual institutions and, above all, the plans of individual students. This study analysed the experiences of 21 Polish students who spent their Erasmus scholarship in Portugal. While the authors concentrated on the specifics of this given location, it did not constitute their only point of attention. The authors analyzed the students’ expectations, comparing them later with their evaluation of the benefits that emerged from their stay. The main question was whether the effects noted by the students corresponded with the intentions of the creators of the programme.  They proved to be quite consistent, with some exceptions such as the opportunity to participate in classes in languages other than Portuguese.